2000
DOI: 10.1046/j.1523-536x.2000.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum Nursing Care: A Case Study of Supportive Interventions and Ethical Conflicts

Abstract: Intrapartum nursing care reflected both a medical model of controlling and hastening birth, as well as a supportive, nurturing, and empowering model of practice that used independent clinical judgments and advocacy. Questionable medical care entangled the nurse in these practices and created moral dilemmas and nurse-physician conflicts. The nurse used various strategies to promote the wishes and welfare of the laboring mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 20 publications
(33 reference statements)
0
34
0
2
Order By: Relevance
“…Conflicting descriptions of advocacy were also noted in one study in which nurses described their practice as following the mother's body while also taking action to hasten and control the birth. 12 This study concluded that advocacy entailed a balancing of the needs of the mother within the limitations imposed by a system dominated by a medical model of practice. Goldberg 13 considered the influence of relationship and practice setting on the enactment of advocacy and respect for autonomy.…”
Section: Related Literaturementioning
confidence: 94%
“…Conflicting descriptions of advocacy were also noted in one study in which nurses described their practice as following the mother's body while also taking action to hasten and control the birth. 12 This study concluded that advocacy entailed a balancing of the needs of the mother within the limitations imposed by a system dominated by a medical model of practice. Goldberg 13 considered the influence of relationship and practice setting on the enactment of advocacy and respect for autonomy.…”
Section: Related Literaturementioning
confidence: 94%
“…Two studies were carried out by the same authors. [2431] Nine studies reported the views, attitude, and experiences of women who had labor, however, three studies explored the viewpoints of health care professionals. One study explained the patients’ experience and one study explored the experiences of both midwives and women.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses exist in a medical hierarchy that punishes disobedience (Rice Simpson & Lyndon, 2009), requires obedience (Hellyer, 2007) and regards nurses as doctors' 'hand-maidens' (Castledine, 2008). According to Sleutel (2000), many nurses avoid conflict by relinquishing power to physicians. Anderson (2009) found that many nurses follow orders with which they are uncomfortable because they cannot imagine acting otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…During critical incidents, nurses tend to experience bullying from both physicians and hospital administration (Lazoritz & Carlson, 2008). Since doctors view nurses as subservient (Castledine, 2008), some nurses avoid physician confrontation (Sleutel, 2000) and follow orders they believe will increase patient risks (Anderson, 2009).…”
Section: Risk In the Practice Of Medicine And Childbirthmentioning
confidence: 99%